Global harmonization of vaccine testing requirements: Making elimination of the ATT and TABST a concrete global achievement. (January 2020) - Viviani, Laura; Halder, Marlies; Gruber, Marion; Bruckner, Lukas; Cussler, Klaus; Sanyal, Gautam; Srinivas, Geetha; Goel, Sunil; Kaashoek, Marianne; Litthauer, Derek; Lopes da Silva, Arthur Leonardo; Sakanyan, Elena; et al.
Abstract: This one-day symposium organized by Humane Society International (HSI) brought together 18 international experts from Argentina, Brazil, China, Europe, India, Russia, South Africa and the United States to discuss the elimination of the abnormal toxicity test (ATT) from the testing requirements for human vaccines as well as the target animal batch safety test (TABST) and the laboratory animal batch safety test (LABST) for veterinary vaccines. Participants reported on country-specific regulatory requirements and, where present, the perspectives on waiver and elimination of those tests. In addition, the attendees, with HSI in the role of facilitator, moved to define the barriers to the complete elimination or waiving of these tests. This report expounds the outcomes of the symposium, and introduces a proposed roadmap – populated with country specific activities – for the elimination of these tests. Highlights: Agreement on need to delete abnormal toxicity test. Agreement on need to waive/delete target animal batch safety test. Stakeholders accepting role of change champions to waive/delete those safety tests. Agreement to keep enlarging the number of involved stakeholders.